Transporting Olive Oil in Roman Times: Chromatographic Analysis of Dressel 20 Amphorae from Pax Julia Civitas, Lusitania - Manhita, Ana (2021)
The organic extracts recovered from 14 potsherds of Dressel 20 oil amphorae collected from Pax Julia civitas (Lusitania) were analysed by GC–MS. Biomarkers of plant oils (saturated and unsaturated fatty acids, alcohols and alkanes arising from plant waxes) were identified in ten samples, and Pinaceae spp. pitch biomarkers were also identified in eight samples. The biomarkers identified in the studied Dressel 20 suggest that, even considering re-use, these amphorae should have been used for the same commodity, i.e., storage/transport of a plant oil. The presence of pitch in the amphorae could only be explained if it was used to reduce the porosity of the ceramic paste and minimise the oil diffusion through it.